PERANAN HUMAS PADA SEKRETARIAT DEWAN PERWAKILAN DAERAH (DPRD) KABUPATEN SOLOK - Yenni Jufri; Dian Rizke; Dedi Putra (Jurnal Public Administration, Business and Rural Development Planning, 2020)
Based on the description in the previous chapters, the author draws the following conclusions: 1) The role of public relations at the Secretariat of the Regional Legislative Council (DPRD) of Solok Regency is as a Communicator, Relationship Builder, as Image Builder. 2) Constraints faced in relation to the role of public relations in the Secretariat of the Regional Legislative Council (DPRD) of Solok Regency include the Coordination Pattern, Position, unprofessional public relations human resources or placement not in accordance with their competence, lack of support for facilities and infrastructure in the Public Relations Board. Regional Representatives (DPRD) of Solok Regency due to the lack of availability of funds. 3) Efforts made in overcoming the constraints faced in relation to the role of public relations at the Secretariat of the Regional Legislative Council (DPRD) of Solok Regency include the commitment of the leadership to provide space for PR to work according to their functions so that the pattern of coordination between public relations and other parts can be bind up with good. The position of public relations needs to be maintained even its role must be increased. One of them is by establishing good cooperation and coordination with other parts of a government environment in terms of providing accurate information. Improving the quality of public relations human resources so that professional human resources are born who are placed according to their competencies by providing education and training to the personnel involved in public relations. Providing trainings related to website management for several public relations staff at the Secretariat of the Regional Representative Council (DPRD) of Solok Regency. The Head of the Public Relations Section coordinates with the head of the Solok Regency DPRK skariat in terms of fulfilling and fulfilling the needs of the public relations department for facilities and infrastructure or infrastructure in the PR field and optimizing the existing budget as a supporter in carrying out the PR role